Short term outcomes and complications of distal ulnar ostectomy in 23 juvenile dogs with carpal valgus secondary to discordant radial-ulnar physeal growth - Christopher, Scott (Frontiers in Veterinary Science, 2022)
Objective: The goal of this study was to report short term clinical and radiographic outcomes after distal ulnar ostectomy in dogs with carpal valgus due to discordant radial-ulnar growth Study Design: Retrospective case study Sample group: Client owned dogs under 1 year of age with carpal valgus and open distal radial physes pre-operatively Methods: Medical records from four veterinary referral centers were searched from January 1, 2015 to January 1, 2022 for juvenile dogs that had been treated with distal ulnar ostectomy for carpal valgus due to premature closure of the distal ulnar physis. Patients were excluded if they were skeletally mature at the time of ostectomy; medical records were incomplete; radial physis was closed at surgery; or definitive corrective osteotomy was performed. Radiographs were evaluated pre-operatively and for short term follow up at approximately 8 weeks. Complications and short term clinical outcomes were evaluated also. Results: 31 limbs from 23 dogs were evaluated. Patients ranged from 4 to 10.8 months of age. All dogs presented for visible carpal valgus and varying degrees of thoracic limb lameness. Sixty-four percent of patients showed resolution of lameness while an additional 13% showed an improvement in clinical lameness without complete resolution. Complications were seen in 32% of patients with 70% percent of those being minor, bandage related complications. Radiographically, 38% of limbs showed bridging callus formation of the ostectomy at an average of 7.5 weeks post operatively and 75% percent of patients with elbow incongruity improved radiographically. There was no significant difference in radial joint angles pre-operatively and at the time of follow up. Conclusion: Distal ulnar ostectomy ameliorates lameness in juvenile dogs with premature distal ulnar physeal closure and shows lack of progression of distal carpal valgus deformity, but does not improve joint angulation. Clinical significance: Distal ulnar ostectomy is associated with mild bandage-related complications and halting of progressive limb deformity within the time frame evaluated, and should therefore be considered a treatment for premature closure of the distal ulnar physis. It does not lead to deformity correction at 8 weeks following surgery but is associated with improved elbow congruity.